Berg Water Project : Communication Practices for Governance and Sustainability Improvement - Haas, Lawrence J. M.; Mazzei, Leonardo; O'Leary, Donal T.; Rossouw, Nigel (World Bank, 2012)
The past decade has witnessed a major global shift in thinking about water, including the role that water infrastructure plays in sustainable development. This rethinking aims to better balance the social, economic, and environmental performance aspects in the development and management of large dams. Additionally, it reinforces efforts to combat poverty by ensuring more equitable access to water and energy services. There is also growing appreciation of how broad-based policy reforms come into play and influence decisions around issues related to dams. Apart from democratization of the development process itself, it is increasingly recognized that infrastructure strategies must complement strategies for water, environment, and energy security; they must also address emerging concerns to reduce vulnerability in water resource systems due to the probability of climate change. Communication comes to the forefront in modern approaches to dam planning and management in several respects. Communication is central to multi-stakeholder dialogue and partnerships at all levels needed to achieve sustainability and governance reform in water resource management and infrastructure provision. At the same time, communication drives the advocacy to mobilize political will and public support for beneficial change and continuous improvement in practices. This case study emphasizes that it is important not only to mobilize all opportunities to reconcile water demand and supply in river basins facing increasing levels of water stress, but also to effectively integrate governance and anticorruption reforms and sustainability improvements into all stages of the planning and project cycle-adding value for all stakeholders, not just for some of them.